2016
DOI: 10.5664/jcsm.5704
|View full text |Cite
|
Sign up to set email alerts
|

Medium Increased Risk for Central Sleep Apnea but Not Obstructive Sleep Apnea in Long-Term Opioid Users: A Systematic Review and Meta-Analysis

Abstract: The meta-analysis results suggest that long-term opioid use in OSA patients has a medium effect on central sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…We believe this is the first report of the negative effects of an anticonvulsant drug on respiratory parameters during sleep. The effect sizes for the primary outcomes were greater than those observed in a trial for flurazepam and a meta‐analysis for opioids (Dolly and Block, ; Filiatrault et al ., ). A smaller effect size was also found in a previous study investigating the effects of antipsychotics on AHI (Rishi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We believe this is the first report of the negative effects of an anticonvulsant drug on respiratory parameters during sleep. The effect sizes for the primary outcomes were greater than those observed in a trial for flurazepam and a meta‐analysis for opioids (Dolly and Block, ; Filiatrault et al ., ). A smaller effect size was also found in a previous study investigating the effects of antipsychotics on AHI (Rishi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…SDB associated with long-term opioid therapy in adults without cancer has also been widely reported 11,13 although the precise nature of such disorders has not been clearly defined. A recent systematic review 31 suggested that opioids were associated with a moderately increased risk of central, but not obstructive, apnea. In contrast, a study in adults receiving methadone observed obstructive apnea to be the dominant abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] There is moderate to strong evidence that opioids, in either acute or chronic cases, can affect both sleep breathing and sleep quality. 3,[14][15][16][17][18][19] However, although the risk of opioids for sleepdisordered breathing is recognized, so far we have failed to identify exactly who is at risk. A 2015 review concludes that CSA is present in 24% of opioid users.…”
Section: Opioid Use and Comedicationsmentioning
confidence: 99%